The Role Of The Legal System And Law Enforcement In Handling Crimes Of Corruption: A Comparative Analysis Of Indonesia, Malaysia, And Thailand - Gaol, Michael Yudhistira Lumban; Majid, Abdul; Afandi, Fachrizal (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The  criminal  act  of  corruption  that  is  rampant  in  the  country  is  not  only  detrimental  to  state  finances  but  is  a  violaton  of  the  social  and  economic  rights  of  society  at  large,  corruption  is  no  longer  a  national  problem,  but  has  become  a  transnational  phenomenon  so  that  internatonal  cooperaton  is  essential  in  preventing  and  eradicating  it.  , in  fact,  for  what  has  been  caused  by  the  crimnal  act  of  corrupton,  extraordinary  efforts  are  needed  in  terms  of  prevention  and  eradication  of  crimnal  acts  of  corruption.  One  of  the  efforts  to  prevent  Indonesia  from  falling  due  to  corruption  is  to  confiscate  and  return  assets  resulting  from  corrupton  crimes  based  on  the  laws  and  regulations  in  force in  the  Indonesan  legal  system.  in  Indonesia,  there  is  no  uinfied  institution  that  has  the  right  to  deal  with  corruption.  The  eradication  of  corruption  in  Indonesia  is  carred  out  by  3  state  institutions,  namely  the  Attorney  General's  Office,  the  Police,  and  the  Corrupton  Eradication  Commission  (KPK).  The  eradication  of  corruption in  one  country  will  not  run  optimally  if  it  is  not  supported  by  the  government's  political  will  to  eradicate  corruption,  the  unity  of  state  institutions  that  eradicate  corrupton,  and  the  enforcement  of  existing  corrupton  eradication  regulations.